Pengaruh Mutu Pelayanan Terhadap Loylitas Pelanggan di Instalasi Rawat Jalan Rumah Sakit Bhayangkara Brimob tahun 2018 - Yurita Mailintina; Sandra Dewi; Fresley Hutapea (Universitas Respati Indonesia, 2019)
Background: Outpatient Installation (IRJ) is a functional unit that handles patient admissions in hospitals, both those who are going for outpatient treatment and those who will be hospitalized. Service delivery in the IRJ was first conducted at the ticket window managed by the Outpatient Medical Record. One of the dimensions of the quality of health services is access to services marked by patient waiting time.Method: This study used analytical quantitative research with observational analytic method and cross sectional survey research design. The research subjects were patients who did not visit the Bhayangkara Brimob Hospital outpatient installation in July to August 2018 as many as 100 people. Data collection using a questionnaire.Results: It was found that the therapeutic function partially affected the re-visit at the Bhayangkara Hospital Brimob Outpatient Installation. This is indicated by the value of Sig = 0.023 <0.05 reject Ho means that there is a relationship between the therapeutic function of the re-visit.Conclusions and Suggestions: From further testing found that therapeutic function affects the return visit at the outpatient installation of Bhayangkara Brimob Hospital. For further research it is expected to use more variables.Keywords: Service Quality and Customer Loyalty.Bibliography: 83 (2000-2017)